(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2018)
There has been a great concern that trainees are seldom observed, instructed, assessed and provide feedback during their training period. It is customary that most of the post graduate institute relies on end of assessment or so called single shot final assessment and pass or fail is the only outcome. Recent trends in medical education states on giving importance of formative assessment and in training assessment. As physicians become ever busier in their own clinical practice, being effective teachers becomes more challenging in the context of expanding clinical responsibilities and shrinking time for teaching. Trainers are often unaware of their role for the trainees. They often reluctant to assess the trainees due to lack of monitoring at faculty level. Now a day trainees are assessed mainly on non documented methods and not in a structured way. Moreover there is little if any feedback is being given to them. The modern medical education given emphasize on workplace-based assessment rather than end of assessment or final assessment. J Bangladesh Coll Phys Surg 2018; 36(4): 159-165